Dynamic property analysis and development of composite concrete floor (CCF) and vibration serviceability : a review - Hamdan, S.; Hoque, M.N; Sutan, N.M (Academic Journals, 2011)
This review article concerns floor vibration, describes the nature of floor vibration and provides options for avoiding it through design, or in the case of existing buildings, reducing or eliminating it through alterations. Excessive floor vibration has become a greater problem as new rhythmic activities, such as aerobics, generators, air conditioners and long-span floor structures have become more common. The current push towards stronger concrete materials and the use of prestressing is resulting in increasing fineness and dynamism of long-span concrete floors in buildings. Although concrete floors have a good vibration serviceability track record, this trend may lead to an increasing number of floors failing their vibration serviceability. There is a current trend towards ever more slender concrete floor structures, which is resulting in more frequent problems with their vibration serviceability. Predictive methods for vibration serviceability must consider not only the structures themselves, but also the non-structural elements which are attached to them, as these may have a significant effect on the dynamic characteristics of the floor structural system. As there has been very little past research in this area, this article describes an investigation into the effects of raised access floors on the vibration serviceability of long-span concrete floors.